EFFECTS OF RELAXATION THERAPY TO LOWER ANXIETY - Rika Istiqamah Matondang (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2020)
This research aims to determine the effect of relaxation to reduce anxiety. Subjects in this study amounted to five six adults who are female and aged 20-45 years. The method used in this study is an experimental method with a one group pretest-posttest research design using purposive sampling technique. The research instrument used the BAI scale (Beck Anxiety Inventory) by Beck & Steer (1998) which has consistency with Cronbach 0.92. Based on the results of the non-parametric test with the Wilcoxon analysis technique to see the difference between the pretest and posttest. The results of the analysis obtained were 0.043, the score was <0.05. These results indicate that there is a decrease in the participants' anxiety scores. These results can be concluded that the application of relaxation can reduce anxiety